Individualized home-based exercise programs for older people to reduce falls and improve physical performance: A systematic review and meta-analysis - Hill, Keith; Hunter, S.; Batchelor, F.; Cavalheri, Vinicius; Burton, E. (Elsevier Ireland Ltd, 2015)
There is considerable diversity in the types of exercise programs investigated to reduce falls in older people. The purpose of this paper was to review the effectiveness of individualized (tailored) home-based exercise programs in reducing falls and improving physical performance among older people living in the community. A systematic review and meta-analysis was conducted of randomized or quasi-randomized trials that utilized an individualized home-based exercise program with at least one falls outcome measure reported. Single intervention exercise studies, and multifactorial interventions where results for an exercise intervention were reported independently were included. Two researchers independently rated the quality of each included study. Of 16,871 papers identified from six databases, 12 met all inclusion criteria (11 randomized trials and a pragmatic trial). Study quality overall was high. Sample sizes ranged from 40 to 981, participants had an average age 80.1 years, and although the majority of studies targeted the general older population, several studies included clinical groups as their target (Parkinson's disease, Alzheimer's disease, and hip fracture). The meta-analysis results for the five studies reporting number of fallers found no significant effect of the intervention (RR [95% CI] = 0.93 [0.72-1.21]), although when a sensitivity analysis was performed with one study of participants recently discharged from hospital removed, this result was significant (RR [95% CI] = 0.84 [0.72-0.99]). The meta-analysis also found that intervention led to significant improvements in physical activity, balance, mobility and muscle strength. There were no significant differences for measures of injurious falls or fractures.